Using PLSV (One Variable Linear Equations) Stick Board Learning Media to Increase Student Learning Motivation in Class 6 of SDN 3 JATIWANGI - Khatimah, Husnul; Desyrimayani, Desyrimayani; Nurrabiah, Nurrabiah; Muamar, Muamar; Damayanti, Dinda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research describes how the use of stickboard media iin learning linear equations with one variable hass an impact on the learning motivation of grade 6 students at SDN 3 JATIWANGI. This research uses descriptive qualitative, data is collected through classroom observations, interviews with teachers and students, as well as documentation of student learning outcomes. The results of this research show that the use of keyboard media creates a more interactive and interesting learning environment. Students are more active in participating in learning, more enthusiastic in discussions, and more easily understand the concept of linear equations in one variabel. This is shown by an increase in assignment scores and students’ enthusiasm in participating in lessons.